# cosx-sexc=0

## Simple and best practice solution for cosx-sexc=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cosx-sexc=0 equation:

Simplifying
cosx + -1sexc = 0
Reorder the terms:
-1cesx + cosx = 0
Solving
-1cesx + cosx = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'csx'.
csx(-1e + o) = 0
Subproblem 1Set the factor 'csx' equal to zero and attempt to solve:
Simplifying
csx = 0
Solving
csx = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
csx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1e + o)' equal to zero and attempt to solve:
Simplifying
-1e + o = 0
Solving
-1e + o = 0
Move all terms containing c to the left, all other terms to the right.
Add 'e' to each side of the equation.
-1e + e + o = 0 + e
Combine like terms: -1e + e = 0
0 + o = 0 + e
o = 0 + e
Remove the zero:
o = e
Add '-1o' to each side of the equation.
o + -1o = e + -1o
Combine like terms: o + -1o = 0
0 = e + -1o
Simplifying
0 = e + -1o
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`